Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/3695848
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Fluid Mesenchymal Stem Cell-Derived Exosomes Inhibit Apoptosis in Ovarian Granulosa Cell via miR-369-3p/YAF2/PDCD5/p53 Pathway

Abstract: Human amniotic fluid stem cell-derived exosome (HuAFSC-exosome) transplantation is considered a promising treatment for premature ovarian failure (POF). However, its mechanism remains unclear. In this study, exosomes were isolated and enriched from HuAFSC subsets of CD44+/CD105+, and the exosomes were transplanted into a POF model in vitro and in vivo. Our results confirmed that the exosomes produced by CD44+/CD105+ HuAFSCs could achieve therapeutic effects in a mouse POF model. Our research also showed that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In the apoptotic signaling network, the p53 signaling pathway regulates the expression of pro-apoptotic genes, including Bax, Bak, Bad, and Apaf-1. However, miR-369-3p, miR-644-5p, and miR-125b-5p in MSCs-Exos exert antiapoptotic effects by inhibiting the activation of p53 [ 32 , 55 57 ]. And interestingly, miR-455-3p and miR-19a exhibit antiapoptotic effects by inhibiting JNK and subsequent activation of p53 and caspase-3 [ 58 , 59 ].…”
Section: Mscs Protect Cells From Apoptosismentioning
confidence: 99%
“…In the apoptotic signaling network, the p53 signaling pathway regulates the expression of pro-apoptotic genes, including Bax, Bak, Bad, and Apaf-1. However, miR-369-3p, miR-644-5p, and miR-125b-5p in MSCs-Exos exert antiapoptotic effects by inhibiting the activation of p53 [ 32 , 55 57 ]. And interestingly, miR-455-3p and miR-19a exhibit antiapoptotic effects by inhibiting JNK and subsequent activation of p53 and caspase-3 [ 58 , 59 ].…”
Section: Mscs Protect Cells From Apoptosismentioning
confidence: 99%
“…miRNA is a distinct class of small (approximately 22 nucleotides), single-stranded, and non-coding RNAs, and play critical functions in the regulation of cellular gene expression by binding to complementary sequences in the target mRNAs, leading to either translational repression or target degradation of the specific mRNAs ( Ha and Kim, 2014 ). Several studies indicate that miRNA carried by EVs plays a key role in the treatment of POI ( Xiao et al, 2016 ; Ding et al, 2020 ; Geng et al, 2022b ; Cai et al, 2022 ). In the following section, we explore the potential mechanisms and application value of different EVs ( Figure 1 ).…”
Section: The Pathogenesis Of Poi and The Application Of Stem Cell-der...mentioning
confidence: 99%
“…Subsequently, AFSCs-EVs are isolated and used in POI. Geng et al (2022b) indicate that CD44+/CD105+ human AFSC-EVs carrying miR-369-3p could specifically downregulate the expression of YAF2, inhibit the stability of PDCD5/p53, and reduce the apoptosis of OGCs, thereby exerting therapeutic effects on POI. In addition, compared with BMSCs, AFSCs secreted higher levels of EVs ( Tracy et al, 2019 ).…”
Section: Amniotic Fluid Stem Cell-derived Evs (Afscs-evs)mentioning
confidence: 99%
“…Obviously, the diverse spectrum of factors secreted by fetal stem cells (Table 1 ) already suggested that their restorative potential could be composed of many different mediators. Although the according research is still in its infancy, some signalling cascades including the nerve growth factor (NGF)/tropomyosin receptor kinase (TrkA) pathway [ 163 ], the phosphoinositide 3-kinase (PI3K) pathway [ 167 ], the transforming growth factor β1 (TGFβ1)/SMAD3 pathway [ 168 ], the bone morphogenetic protein (BMP)/SMAD pathway [ 169 ], epidermal growth factor (EGF)-mediated nuclear factor erythroid 2-related factor 2 (NRF2) /heme oxygenase-1 (HO-1) activation [ 170 ], the forkhead-box-protein O3 (FOXO3) pathway [ 167 ], the miR-369-3p/YY1-associated factor 2 (YAF2)/programmed cell death 5 (PDCD5)/p53 pathway [ 171 ], as well as the function of the hepatocyte growth factor (HGF) [ 172 ], epidermal growth factor (EGF) [ 172 ], or vascular endothelial growth factor (VEGF) [ 173 ], have already been demonstrated to be involved in the here discussed fetal stem cell-mediated curative processes (see also Table 3 ).…”
Section: Multipotent Fetal Stem Cells As New Therapeutic Tools For Re...mentioning
confidence: 99%